Psychological Differences between Men and Women: Nature vs. Nurture - Chu, Tsz Tung (Scarlett) (Journal of Student Research, 2022)
Psychological differences between men and women have generated a lot of interest, yet the debate over their existence and potential causes has not yet been resolved. This article presents and reviews various literatures analyzing gender psychological differences between men and women. Furthermore, this work considers the various factors that lead to gender differentiation in both biological and societal contexts. Understanding such psychological differences between the sexes has strong clinical implications, and further investigation into the impact of social and biological influences on the sexes’ psychologies is necessary to implement such findings in clinical scenarios.